The Application Of English Songs To Improve Student’s Listening Comprehension - Kawalo, Octaviona S. S; Rorimpandey, Rinny; Wongkar, Yapi (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
Listening comprehension is a fundamental skill that involves not just hearing words, but actively understanding and interpreting the meaning behind them. It requires focusing attention, retaining information, and making sense of what is heard in real time. This research investigates the application of English Songs to improve students’ listening Comprehension. Conducted at SMP Negeri 5 Tondano, this research involved 20 class VII students. Using a quantitative approach, this research used a pre-experimental design with one pre-test and post-test group. Data collection relies on tests, with the same format but different songs for the pre-test and post-test. The results showed significant improvement in listening proficiency, with the average post-test score (89,5) surpassing the pre-test score (33). This underlines the potential of English Songs as a tool to improve students’ English listening comprehension